Y Chromosomal Sequences Identified in Gonadal Tissue of Two 45,X Patients with Turner Syndrome - Kocova, Mirjana; Witchel, Selma Feldman; Nalesnik, Michael; Lee, Peter A.; Dickman, Paul S.; MacGillivray, Margaret H.; Reiter, Edward O.; Trucco, Giuliana; Trucco, Massimo (Springer, 1995)
We examined excised gonadal tissue obtained from two 45,X patients for evidence of Y chromosomal material. Both patients had features atypical for individuals with Turner syndrome, a large dysgerminoma in patient 1 and clitoromegaly in patient 2. Southern blot analysis of polymerase chain reaction (PCR)-amplified DNA was performed for five Y chromosome-specific probes (SRY, ZFY. DYZ3, KALY, and DYZ1). Fluorescence in situ hybridization (FISH) with a combination probe specific for the DYZ1/DYZ3 loci was utilized. For both patients, Southern blot analysis of PCR-amplified DNA with primers for the SRY gene was positive. No signals were detected with the other Y chromosome-specific probes for patient 1. For patient 2, positive signals were obtained for all-Y-specific probes. FISH was negative in the gonadal specimen from patient 1, while rare cells were positive in the sections from patient 2. Turner syndrome and mixed gonadal dysgenesis may represent different points on a continuum of disorders of sexual differentiation. Although the risk for gonadal tumors is considered to be low in patients with Turner syndrome, prospective evaluation is critical to ascertain: The frequency of somatic cell mosaicism for cell lines carrying Y chromosomal material, and how the presence of Y chromosomal material in patients with Turner syndrome affects the propensity for virilization and gonadal neoplasms.